The genesis of the electricity supply industry in Britain: A case study of NESCo from 1889 to 1914. Issue 5 (4th July 2017) - McGovern, Tom; McLean, Tom
Abstract: A study of the Newcastle upon Tyne Electric Supply Company (NESCo) provides a micro-history of the emergence of the electricity supply industry in Britain up to the First World War. This research examines the role of social capital in the establishment and growth of NESCo, the only financially successful British electric power company. Temporal bracketing was adopted to evaluate two distinct time periods: emergence from 1889 to 1899; and growth from 1900 to 1914. Family, business and social networks together with geographical and political factors secured the company's dominant position. The structural relationship with Merz & McLellan contributed to growth through acquisitions, joint ventures, and access to new markets.